Seeking treatment for mental illness and substance abuse: A cross-sectional study on attitudes, beliefs, and needs of military personnel with and without mental illness. (March 2022) - Bogaers, Rebecca; Geuze, Elbert; Greenberg, Neil; Leijten, Fenna; Varis, Piia; van Weeghel, Jaap; van de Mheen, Dike; Rozema, Andrea; Brouwers, Evelien
Abstract: Background: Often, military personnel do not seek treatment for mental illness or wait until they reach a crisis point. Effective, selective, and indicated prevention is best achieved by seeking treatment early. Aims: We aimed to examine military personnel's attitudes, beliefs, and needs around seeking treatment for mental illness. We compared those who sought treatment to those who did not and those with and without the intention to seek treatment. Finally, we examined factors associated with intentions of not seeking treatment. Method: We conducted a cross-sectional questionnaire study of military personnel with (N = 324) and without (N = 554) mental illness. Descriptive and regression analyses (logistic and ordinal) were performed. Results: The majority of the personnel believed treatment was effective (91.6%); however, most preferred to solve their own problems (66.0%). For personnel with mental illness, compared to those who sought treatment, those who did not had a higher preference for self-management and found advice from others less important. For those without mental illness, those with no intention to seek treatment indicated a higher preference for self-management, stigma-related concerns, denial of symptoms, lower belief in treatment effectiveness and found it less important to be an example, compared to those with treatment-seeking intentions. A clear indication of where to seek help was the most reported need (95.7%). Regression analyses indicated that not seeking treatment was most strongly related to preference for self-management (OR(95%CI) = 4.36(2.02–9.39); no intention to seek treatment was most strongly related to a lower belief that treatment is effective (OR(95%CI) = .41(0.28–0.59) and with not having had positive earlier experiences with treatment seeking (OR(95%CI) = .34(0.22–0.52). Conclusions: To facilitate (early) treatment seeking, interventions should align with a high preference for self-management, mental illness stigma should be targeted, and a clear indication of where to seek treatment is needed.